PENGARUH PERSEPSI KEGUNAAN, KEMUDAHAN, KEAMANAN DAN KERAHASIAAN, DAN KECEPATAN TERHADAP INTENSITAS PERILAKU DALAM PENGGUNAAN E-FILING (Studi Pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Pekanbaru Senapelan) - Rezky Wahyuni; Kirmizi Ritonga; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted to test whether the perceived of usefulness, perceived of ease, perceived of security and privacy, and perceived of speed affect the behavioral intensity for the e-filing usage. The study was conducted of the personal tax payer listed in KPP Pratama Pekanbaru Senapelan. A total respondents used in this research is 98 respondents. Method of analysis used in this study is multiple regression analysis with SPSS version 20.0. The result of the study showed that perceived of ease, perceived of security and privacy, and perceived of speed affect the behavioral intensity for the e-filing usage. The result of the study also showed that perceived of usefulness does not effect the behavioral intensity for the e-filing usage. The magnitude of the effect caused by Adjusted R2 by four variables together is 72.5% of the dependent variable, while the remaining 27.5% is influenced by other variables not examined in this study.Keywords: E-filing, Behavioral Intensity For The E-filing Usage, Perceived Usefulness, Perceived Ease, Security and Privacy, Speed.